Analisis Kinerja Organisasi di Lingkungan Sekretariat Jenderal Kemendagri - Pangestuti, Azizah Nur Fiqa (Jurnal Ekonomi & Bisnis, 2024)
The Secretariat General of the Ministry of Home Affairs is a public sector organization whose main vision is to be the main driver of good governance in realizing the vision of the Ministry of Home Affairs. This vision is used as a guideline in preparing strategic planning which will later become a performance indicator for the Secretariat General. The performance of an organization is described as the result of a process carried out by the individuals within it based on predetermined plans. Therefore, it is necessary to measure organizational performance to find out whether the organization has achieved its goals or not. The Balanced Scorecard method can measure performance using a financial perspective and a non-financial perspective. The aim of this research is to determine the performance of the Secretariat General using the balanced scorecard method. The research design uses a qualitative descriptive design. Data collection techniques were carried out using observation, interviews and documentation studies with the data used being primary data and secondary data. The research results show that based on the financial perspective, customer perspective, and growth and learning perspective, the performance of the Secretariat General is very good. As for the internal business process perspective, the performance of the Secretariat General is good. These findings indicate that although the Secretariat General has achieved excellent results in most areas, there is still room for improvement in internal business processes to achieve operational excellence.